High-Concentration Synthesis of Ligand-Free Au and Ag Nanoparticles by Nanosecond Laser Ablation and Their Conversion to Au–Ag Alloy Nanoparticles via Femtosecond Laser Processing - Siti Masyithah; Muhandis Shiddiq; Yessie Widya Sari (Jurnal Ilmu Fisika, 2026)
A laser processing strategy is presented for the high-concentration synthesis of ligand-free Au, Ag, and Au–Ag alloy nanoparticles. Monometallic Au and Ag nanoparticles were first synthesized independently by nanosecond pulsed laser ablation in liquid (PLAL), producing stable ligand-free colloids. The Au and Ag colloids were then mixed in an equimolar ratio and irradiated with femtosecond laser pulses to induce alloy formation without chemical stabilizers or reducing agents. Ultraviolet–visible (UV–vis) spectroscopy shows a single localized surface plasmon resonance peak that shifts from 400 nm (Ag) to 509 nm (Au), with the Au–Ag alloy peak located between the two, confirming alloy formation. Transmission electron microscopy (TEM) reveals spherical Au, Au–Ag alloy, and Ag nanoparticles with average diameters of 11.8 ± 8.1 nm, 18.8 ± 5.9 nm, and 20.3 ± 9.4 nm, respectively, with the alloy nanoparticles exhibiting a narrower size distribution. Zeta potential measurements of −36.4, −41.2, and −48.1 mV for Ag, Au, and Au–Ag nanoparticles indicate good colloidal stability, with the alloy nanoparticles showing the highest stability. This laser-based approach provides a chemical-free route for producing high-concentration noble metal and alloy nanoparticles with tunable plasmonic and colloidal properties.